Merti Dusun ceremony as a local culture-based strategy for strengthening elementary character education - Sunarsih Sunarsih; Sriyanto Sriyanto (Jurnal Prima Edukasia, 2026)
: Character education in schools base own fundamental role in form a generation of integrity and empowerment competitive and moral noble . In line with increasing global attention to education characters , various studies show importance integration values culture local For strengthen relevance and meaning learning for participant educate . This study focused on exploration values education character in tradition Merti Dusun as form wisdom local Indonesian society that reflects harmony between humans , nature , and spirituality . Tradition This involving various activity collective like prayer together , procession culture , feasts , and cross-country mutual cooperation generation , which reflects values like Work same , responsibility responsibility , mutual cooperation, and gratitude . Approach qualitative with perspective ethnopedagogy used For dig meaning and relevance values the in context education basis . Study results show that Merti Dusun No only functioning as inheritance culture , but also as means effective For implant values character through experience contextual social and spiritual values . Integration of values culture local to in learning at school base proven can increase sensitivity culture , strengthening identity national , and encourage creation education more characters​ contextual , sustainable , and adaptive to global dynamics . Findings This confirm importance involvement community and culture local in design curriculum education characters in Indonesia.